A non-acid-assisted and non-hydroxyl-radical-related catalytic ozonation with ceria supported copper oxide in efficient oxalate degradation in water - Zhang, T.; Li, W.; Croue, Jean-Philippe (Elsevier BV, 2012)
Oxalate is usually used as a refractory model compound that cannot be effectively removed by ozone and hydroxyl radical oxidation in water. In this study, we found that ceria supported CuO significantly improved oxalate degradation in reaction with ozone. The optimum CuO loading amount was 12%. The molar ratio of oxalate removed/ozone consumption reached 0.84. The catalytic ozonation was most effective in a neutral pH range (6.7-7.9) and became ineffective when the water solution was acidic or alkaline. Moreover, bicarbonate, a ubiquitous hydroxyl radical scavenger in natural waters, significantly improved the catalytic degradation of oxalate. Therefore, the degradation relies on neither hydroxyl radical oxidation nor acid assistance, two pathways usually proposed for catalytic ozonation. These special characters of the catalyst make it suitable to be potentially used for practical degradation of refractory hydrophilic organic matter and compounds in water and wastewater. With in situ characterization, the new surface Cu(II) formed from ozone oxidation of the trace Cu(I) of the catalyst was found to be an active site in coordination with oxalate forming multi-dentate surface complex. It is proposed that the complex can be further oxidized by molecular ozone and then decomposes through intra-molecular electron transfer. The ceria support enhanced the activity of the surface Cu(I)/Cu(II) in this process. © 2012 Elsevier B.V.